Changes in motor unit firing pattern are associated with post‐exercise blood pressure response in older untreated but not treated hypertensive adults - Ryosuke Takeda; Tetsuya Hirono; Akito Yoshiko; Shun Kunugi; Masamichi Okudaira; Saeko Ueda; Taichi Nishikawa; Kohei Watanabe (Experimental Physiology)
Abstract This study aimed to determine the difference in motor unit (MU) firing pattern between hypertensive and normotensive individuals, and the relationship between MU firing pattern and post‐exercise blood pressure (BP) response in older individuals. Fourteen older untreated (systolic/diastolic BP (SBP/DBP) ≥ 130/80 mmHg, 76 (5) years), 11 treated hypertensive (78 (4) years) and 14 normotensive (SBP/DBP < 130/80 mmHg, 71 (4) years) individuals were studied. Participants performed ramp‐up exercises until 50% of maximal voluntary contraction (MVC) of knee extension and five MVCs. During the ramp‐up exercise, high‐density surface electromyography signals were recorded and each MU firing rate (FR) and recruitment threshold was assessed. The slope of the linear regression between MUFRs and recruitment thresholds was calculated to assess the MU firing pattern. Pre‐ and post‐exercise blood pressure was measured. Change in (∆)SBP from pre‐ to post‐exercise was greater in treated hypertensive than untreated hypertensive individuals (P = 0.026). MUFR was lower in treated hypertensive than untreated hypertensive and normotensive individuals (P < 0.001). Although the slope was not significantly different between groups (P = 0.294), FRs of larger MUs were lower than those of smaller MUs in treated hypertensive and normotensive individuals (P < 0.05) but sustained in untreated hypertensive individuals. The FRs of larger MUs and slope were positively correlated with the ∆SBP only in hypertensive individuals (r = 0.768 and 0.715; P = 0.044 and 0.020). MUFR was lower in treated hypertensive than untreated hypertensive and normotensive individuals. Furthermore, MU firing patterns were associated with the ∆SBP after exercise in older untreated hypertensive individuals, but this relationship was not observed in treated hypertensive and normotensive individuals.